The Reason for “Gender expression” in the Legal Corpus. A Contribution to the Preservation of the Right of the Subject that Practices Cross-dressing - Barbé i Serra, Alba (Revista de Antropología Social, 2017)
This article attempts an approach to the relationship between the Hate Crimes and the integral preservation of the rights of people who practice cross-dressing in Catalan and Spanish context. Beyond understanding that the defence of the subject is framed within the field of fundamental Human Rights, we would like to provide a work proposal in the legislative approach to Transphobic violence, and therefore gender violence, while collecting the empirical diversity of its manifestations.